Estimation of Gestational Age via Image Analysis of Anterior Lens Capsule Vascularity in Preterm Infants: A Pilot Study - Patel, Monalisa; Mukherjee, Dibyendu; Farsiu, Sina; Munoz, Breda; Blood, Arlin B.; Wilson, Christopher G.; Griffin, Jennifer B. (Frontiers in Pediatrics, 2019)
Intro Anterior lens capsule vascularity (ALCV) is resorbed in the developing fetus from 27 to 35 weeks gestation. In this pilot study, we evaluated the feasibility and validity of combining smartphone ophthalmoscope videos of ALCV and image analysis for gestational age estimation. Methods ALCV videos were captured longitudinally in preterm neonates from delivery using a PanOptic® Ophthalmoscope with an iExaminer® adapter (Welch-Allyn). ALCV video frames were manually selected and quantified using semi-automatic image analysis. A predictive model based on ALCV features was compared to gold-standard ultrasound gestational age estimates. Results A total of 64 image-capture sessions were carried out in 24 neonates. Ultrasound-estimated gestational age and ALCV-predicted gestational age estimates indicate that the two methods are similar (r=0.78, p<0.0001). ALCV estimates of gestational age were within 0.11 ± 1.3 weeks of ultrasound estimates. In the final model, gestational age was predicted within ±1 week for 54% and within ±2 weeks for 86% of the measures. Conclusions This novel application of smartphone ophthalmoscopy and ALCV image analysis may provide a safe, accurate and noninvasive technology to estimate postnatal gestational age, especially in low income countries where gestational age may not be known at birth.